EVOLUTION ON THE TERM NON GOVERNMENTAL ORGANIZATION (NGO) - Olivo U., Maria (Revista Venezolana de Análisis de Coyuntura, 2016)
One of the terms used to describe many Non Profit Organizations is Non Governmental Organization (NGO). Perhaps on account of the recent emergence of the field of Non Governmental Organizations, a multitude of generic terms are used to describe heterogeneous organizations. This imprecise usage often impedes the understanding of what the term NGOs means, and how it should be applied.The term "NGOs" is habitually used by multilateral entities, bilateral entities, private organizations and in all countries around de world. We can ask ourselves: What does the term Non Governmental Organizations mean? How was this term derived? How has this term, NGOs been developed? While the use of generic terms can be valid under certain circumstances, their use can also entail serious problems when used in certain fields of study or research. It is impossible to analyze a phenomenon or to establish a research methodology and reach reasonable conclusions if the factors that the terminology implies are not clearly defined, in terms of both their internal structure and their effects. In this essay I will examine the origin, development and meaning of the term Non Governmental Organization from XIX Century to 1990 decade and whether it is accurately used in the different fields in which it is commonly applied today. First, the origin of the term NGOs will be analyzed. Second, the use of this term in the world and, finally its various usage of meaning according to different organizations or countries.